Multiple disease resistance in wheat and triticale - R. AGGARWAL; S.K. JAIN, P. BAHADUR, D.V. SINGH, K.D. SRIVASTAVA (Indian Phytopathology, 2002)
Evaluation of wheat and triticale entries for resistance to various diseases under high fertilizer treatment (NPK 120:60:40) at Dhaulakuan, Himachal Pradesh, and Delhi, India, during rabi 1992-94 revealed that DW 698, DW 776, DW 777, DW 812, MPO 215, PG’S’ GGO-VZ 380 X 885 X CR’S’, TWB’S’ and WH 805 showed multiple disease resistance to leaf and stripe rusts (caused by Puccinia recondita and P. striiformis, respectively), powdery mildew (Erysiphe graminis), Karnal bunt (Tilletia indica) and loose smut (Ustilago segetum var. tritici). Entries DW 776, DW 777, DW 812 and WH 805 also showed resistance to stem rust (caused by P. graminis). Thirteen entries, CMH-76-1330/TTU-RA/CMH 74A-370, Harlan 2735, H 567.71/3PAR-CMH-7730B 1Y-4B-1Y-1B-2B-1Y-0Y, ISWRN160, ND 589, PBW 34, PBW 320, Shangai-7313 OY, Teal’S’/Win// GAD’S’, THB’S’ F 11915, TL 2597 and VEE ’S’/MJI exhibited resistance to leaf and stripe rusts, powdery mildew and Karnal bunt, while DW 844, ND 602, WH 581 and WH 585 showed resistance to leaf and stripe rusts and powdery mildew. PBW 34 also showed resistance to stem rust. It is suggested that the resistance of above sources could be used in breeding for multiple disease resistance.